The role of nomination committee in selecting diversified board : the case of Malaysia / Kashan Pirzada - Pirzada, Kashan (2017)
Board diversity has grown in importance as a result of the global financial crisis of 2008. Board diversity is a company requirement in Malaysian companies and in relation to this, the Malaysian Code of Corporate Governance 2012 requires that it is the responsibility of the nomination committee (NC) to select a board of directors who are from diverse backgrounds. This study attempts to examine the impact that female directors in the NC have on gender diversity as well as to observe Malay, Chinese and Indian directors’ presence in the NC have any influence on ethnic diversity which can affect how the board is run. For the purpose of this study which used quantitative methodology to analyse, 393 (50%) of non-financial Malaysian listed companies for the 3 year period of 2011 to 2013, were selected as samples. Based on the analysis of the data, it was found that the presence of female directors in the NC of an organization is significantly related to the level of gender diversity on the board. The results signified the importance of having female directors in the NC as their presence can influence gender diversity on the board. The results shown by the ethnicity diversity model indicates that, a higher proportion of Indian, as compared with Malay and Chinese directors, on the NC is significantly related to the ethnic diversity on the board. Further, the proportion of executive directors in the NC was also found to have a significant impact on the Malay, Chinese and Indian directors’ nomination process but does not a significantly impact on female directors. To test the robustness of the models, several sets of measures were used. Issues of normality of residuals, homoscedasticity, multicollinearity and endogeneity were then addressed by using a fixed effect model of panel data analysis (1) and the generalized method of moments (2). From this study, it can be concluded that the results drawn support the social identity theory and power struggle theory which illustrate the importance of diversity in the NC of Malaysian companies as a means to create an unbiased and effective board mix.